I'm - Deborah Roberts this catalog accompanies the exhibition Deborah Roberts: I'm - Whitley, Zoe; Walker, Darren (The Contemporary Austin, 2021)
Foreword / by Darren Walker -- Acknowledgments / by Heather Pesanti -- Reclaiming the "I" / by Heather Pesanti -- Let us now praise Deborah Roberts / by Eddie Chambers -- Euphoria and tragedy / Deborah Roberts and Zoé Whitley in conversation -- Color plates -- List of works -- Artist and author biographies -- The Contempory Austin Board and staff -- Credits.
Exhibition dates: The Contemporary Austin, January 23-August 15, 2021, Museum of Contemporary Art Denver, September 10, 2021-January 30, 2022 ; Art + Practice, in collaboration with the California African American Museum, March 19-August 20, 2022 ; Cummer Museum of Art & Gardens, September 16-December 4, 2022
Keywords: Roberts, Deborah -- 1962-; Mixed media; Collage; Person of Color -- Motiv; Roberts, Deborah / 1962- / Exhibitions; Roberts, Deborah / 1962- / Interviews; Collage / Art / 21st century / Exhibitions; Mixed media (Art) / 21st century / Exhibitions; African American art; African American women artists; Children, Black, in art; exhibition catalogs; Bildband; Ausstellungskatalog -- The Contemporary Austin -- Austin -- 23.01.2021-15.08.2021; Ausstellungskatalog -- Museum of Contemporary Art Denver -- Denver -- 10.09.2021-30.01.2022; Ausstellungskatalog -- California African American Museum -- Los Angeles -- 19.03.2022-20.08.2022; Ausstellungskatalog -- Cummer Museum of Art & Gardens -- Jacksonville -- 16.09.2022-04.10.2022